Solomon Islands : Staff Report for the 2013 Article IV consultation and Second Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criterion. (IMF Staff Country Reports; Country Report, 2014)
This Information Annex highlights that the Solomon Islands has recovered well from a precarious position during the global economic crisis. Growth has accelerated rapidly and international and fiscal reserves increased, on the back of increased logging and mining, but also owing to better fiscal management and increased international assistance. The medium-term reform agenda under the Core Economic Working Group emphasizes, among other things, strengthening of public financial management, in particular with regard to the management of natural resource revenues. Significant amounts of support have been provided to the Central Bank of Solomon Islands in formulating and implementing new prudential regulations for banks and also in developing a more robust inflation forecasting regime.